2017
DOI: 10.1007/s10680-017-9445-1
|View full text |Cite
|
Sign up to set email alerts
|

Cognition, Health, and Well-Being in a Rural Sub-Saharan African Population

Abstract: Cognitive health is an important dimension of well-being in older ages, but few studies have investigated the demography of cognitive health in sub-Saharan Africa’s (SSA) growing population of mature adults (= persons age 45+). We use data from the Malawi Longitudinal Study of Families and Health (MLSFH) to document the age and gender patterns of cognitive health, the contextual and life-course correlates of poor cognitive health, and the understudied linkages between cognitive and physical/mental well-being. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 64 publications
3
13
0
Order By: Relevance
“…More research should be done to identify which types of cognitive outcomes were most improved as a result of the intervention, as we only analyzed overall measures of cognition because the specific outcomes examined were variable and too few studies were available to compare specific variables (such as working memory). Identifying the impact of specific cognitive outcomes is important because HIV OVC tend to demonstrate some vulnerabilities in their cognitive performance, which, in turn, can affect their well-being and motivation at school (Payne, Kohler, Bandawe, Lawler, & Kohler, 2018), and their ability to complete health-related tasks such as adhering to medication (Malee et al, 2009). For example, perhaps surprisingly, verbal impairment and reading difficulties actually predicted better adherence (Nichols et al, 2012); the mechanism of this association is not clear, but this may be related to having less responsibility for their medication as its delivery might be controlled by adults.…”
Section: Discussionmentioning
confidence: 99%
“…More research should be done to identify which types of cognitive outcomes were most improved as a result of the intervention, as we only analyzed overall measures of cognition because the specific outcomes examined were variable and too few studies were available to compare specific variables (such as working memory). Identifying the impact of specific cognitive outcomes is important because HIV OVC tend to demonstrate some vulnerabilities in their cognitive performance, which, in turn, can affect their well-being and motivation at school (Payne, Kohler, Bandawe, Lawler, & Kohler, 2018), and their ability to complete health-related tasks such as adhering to medication (Malee et al, 2009). For example, perhaps surprisingly, verbal impairment and reading difficulties actually predicted better adherence (Nichols et al, 2012); the mechanism of this association is not clear, but this may be related to having less responsibility for their medication as its delivery might be controlled by adults.…”
Section: Discussionmentioning
confidence: 99%
“… 9 The loss of nutritional intake in old age is also potentially linked to the deterioration in cognitive health and skills of the elderly in Africa recently reported in Payne et al . (2013, 2016), a relation that we think deserves further exploration. This is relevant for policy as SSA is aging [Payne et al .…”
mentioning
confidence: 92%
“…Cross-sectional analyses of the 2012/2013 data found that women have substantially worse cognitive health than men, and experience a steeper age gradient in cognitive abilities. 8 Strong social ties and exposure to socially complex environments were associated with higher cognitive health, as was higher life-course socioeconomic status. Poor cognitive health is associated with adverse outcomes such as less nutrition intake, lower income and reduced work efforts.…”
Section: Findings To Datementioning
confidence: 99%
“…Cohort analyses also confirm the patterns of cognitive decline as individuals become older over time, which had previously been suggested—but not confirmed—based on cross-sectional 2012/2013 analyses. 8 …”
Section: Findings To Datementioning
confidence: 99%
See 1 more Smart Citation